Synthesis of Aminonaphthalenes from Morita–Baylis–Hillman Carbonates via 6π‐Electrocyclization of Ketenimine Intermediates. (16th June 2016) - Min, Beom Kyu; Roh, Hwa Jung; Ryu, Ji Yeon; Lee, Junseong; Kim, Jae Nyoung
Abstract :